A zeolite imidazolate framework-derived electrocatalyst, preparation method and application thereof
By growing in situ on the carbon nanotube membrane and heat-treated nickel-zinc double-doped ZIF8@ZIF67 particles, the problem of insufficient conductivity and catalytic performance of ZIF materials is solved, and efficient hydrogen production and oxygen production performance of electrolytic water is achieved.
Patent Information
- Application Number
- CN202211591681.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-12
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-12-12
AI Technical Summary
The conductivity and catalytic performance of ZIF materials in the field of electrocatalysis lead to problems such as large impedance and low current conduction during the electrolytic water hydrogen production and oxygen production process.
The conductive properties of the catalyst are improved by growing nickel-zinc double-doped ZIF8@ZIF67 particles in situ on the carbon nanotube membrane and carbonize the surface through heat treatment.
It achieves low impedance and high catalytic activity, improves the performance of hydrogen and oxygen production in electrolytic water, making it an ideal electrolytic water catalytic material.
Smart Images

Figure CN115874217B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalysts for producing hydrogen and oxygen by electrolyzing water, and in particular relates to a zeolite imidazolate skeleton-derived electrocatalyst, a preparation method and application thereof. Background Art
[0002] Recently, hydrogen energy has received widespread attention as an important new energy source. At present, the electrocatalytic hydrogen evolution reaction (HER) and the electrocatalytic oxygen evolution reaction (OER) are the simplest and cleanest methods for preparing hydrogen and oxygen, but the energy barrier of direct water electrolysis is relatively high, so it is necessary to research and develop suitable electrochemical catalysts to reduce the energy barrier of water electrolysis. Precious metal materials represented by platinum are high-performance water electrolysis catalysts, but precious metal reserves are scarce and expensive, so it is necessary to research and develop water electrolysis catalysts based on non-precious metal materials.
[0003] Metal-organic framework materials (MOFs) with non-precious metals as the core have good catalytic activity. Among them, the zeolite imidazolate framework (ZIF) material with high stability is considered to have broad development prospects in the field of catalytic electrolysis of water to produce hydrogen and oxygen. However, the chemical bonds in ZIF materials are mainly coordination bonds, and their application in the field of electrocatalysis will result in large impedance and difficulty in conducting low currents. In terms of catalytic activity, although the performance of ZIF materials is relatively outstanding, there is still a certain gap compared with industrial precious metal catalysts. Therefore, in practical applications, how to improve the conductivity and catalytic performance of ZIF materials to promote their further application in the field of electrocatalysis is a problem that needs to be solved at present. Summary of the invention
[0004] The purpose of the present invention is to solve the problems of poor conductivity and catalytic performance of current ZIF materials, and to provide a zeolite imidazolate framework-derived electrocatalyst, a preparation method and application thereof. The electrocatalyst has low impedance, high catalytic activity, good hydrogen and oxygen evolution performance, and is an ideal catalytic material for water electrolysis.
[0005] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a zeolite imidazolate framework-derived bifunctional electrocatalyst, comprising the following steps:
[0006] S1. dispersing the carbon nanotube film, the dispersant, the cobalt salt, the nickel salt, and the zinc salt in a first solvent to obtain a first solution;
[0007] S2. dispersing dimethylimidazole in a second solvent to obtain a second solution;
[0008] S3. adding the first solution to the second solution to obtain a precursor solution;
[0009] S4. subjecting the precursor solution to a hydrothermal reaction, separating the solid product, washing it, and drying it to obtain ZIF8@ZIF67 / CNTF;
[0010] S5. calcining ZIF8@ZIF67 / CNTF under an inert atmosphere to obtain the zeolite imidazolate framework-derived electrocatalyst.
[0011] Preferably, the carbon nanotube film is a multi-walled carbon nanotube film.
[0012] Preferably, the Co in the cobalt salt 2+ , Ni in the nickel salt 2+ and Zn in the zinc salt 2+ The molar ratio between the carbon nanotube film and the cobalt salt is 2: (1 to 1.5): (1 to 1.5); 2+ The molar ratio is (1~3):1.
[0013] Preferably, the first solvent and / or the second solvent is methanol.
[0014] Preferably, the dispersant is polyvinyl pyrrolidone.
[0015] Preferably, dimethylimidazole and the cobalt salt Co 2+ The molar ratio is (1~2.5):1.
[0016] Preferably, the method further comprises acid washing the carbon nanotube film before step S1.
[0017] Preferably, the temperature of the hydrothermal reaction is 70-110° C. and the time is 5-7 hours.
[0018] Preferably, the calcination conditions are to increase the temperature to 600-950° C. at a heating rate of 1-2.5° C. / min and calcine for 2-6 hours.
[0019] The second aspect of the present invention provides a zeolite imidazolate framework-derived electrocatalyst prepared by the above-mentioned preparation method.
[0020] The third aspect of the present invention provides an application of the above-mentioned zeolite imidazolate framework-derived electrocatalyst for catalytic electrolysis of water to produce hydrogen and / or oxygen.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of the present invention uses carbon nanotubes as a substrate, in-situ grows nickel-zinc dual-doped ZIF8@ZIF67 particles on the surface of the carbon nanotubes, so that the ZIF particles are in-situ grown on the carbon nanotube film, and the contact resistance between the ZIF particles and the substrate is reduced as much as possible. Compared with other self-supporting materials (such as nickel foam, copper mesh, etc.), the carbon nanotube film is used as the substrate, which will not be oxidized at high temperature, so it can be ensured that it still has good self-support and conductivity after heat treatment; wherein the precursor for growing the ZIF particles contains Co 2+ 、Ni 2+ and Zn 2+ ions, among which Co is the absolute active center for HER and OER, and Ni 2+ and Zn 2+ Ions act as a bridge to regulate electronic structure and build accelerated electron transfer channels, which accelerates the catalytic reaction. Through heat treatment, the surface of the in-situ grown ZIF particles is carbonized without destroying their morphology, effectively improving the conductivity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It's Ni 2+ SEM image of the morphology of the single-doped zeolite imidazolate framework-derived electrocatalyst;
[0024] Figure 2 Zn 2+ SEM image of the morphology of the single-doped zeolite imidazolate framework-derived electrocatalyst;
[0025] Figure 3 It's Ni 2+ Zn 2+ SEM image of the morphology of the ion-dual-doped zeolite imidazolate framework-derived electrocatalyst;
[0026] Figure 4 HER polarization curves of electrocatalysts derived from single-doped and double-doped zeolite imidazolate frameworks;
[0027] Figure 5 OER polarization curves of electrocatalysts derived from single-doped and double-doped zeolite imidazolate frameworks. DETAILED DESCRIPTION
[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] A first aspect of an embodiment of the present invention provides a method for preparing a zeolite imidazolate framework-derived electrocatalyst, comprising the following steps:
[0030] S1. dispersing the carbon nanotube film, the dispersant, the cobalt salt, the nickel salt, and the zinc salt in a first solvent to obtain a first solution;
[0031] S2. dispersing dimethylimidazole in a second solvent to obtain a second solution;
[0032] S3. adding the first solution to the second solution to obtain a precursor solution;
[0033] S4. subjecting the precursor solution to a hydrothermal reaction, separating the solid product, washing it, and drying it to obtain ZIF8@ZIF67 / CNTF;
[0034] S5. calcining ZIF8@ZIF67 / CNTF under an inert atmosphere to obtain the zeolite imidazolate framework-derived electrocatalyst.
[0035] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of the present invention uses carbon nanotubes as a substrate, and in-situ grows nickel-zinc dual-doped ZIF8@ZIF67 particles on the surface of the carbon nanotubes, so that the ZIF particles are in-situ grown on the carbon nanotube film, and the contact resistance between the ZIF particles and the substrate is reduced as much as possible. In addition, the carbon nanotube film is used as the substrate, and compared with other self-supporting materials (such as nickel foam, copper mesh, etc.), it will not be oxidized under high temperature conditions, so it can be ensured that it still has good self-support and conductivity after heat treatment.
[0036] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of the present invention, wherein the precursor for growing ZIF particles contains Co 2+ 、Ni 2+ and Zn 2+ ions, among which Co is the absolute active center for HER and OER, and Ni 2+ and Zn 2+ Ions act as a bridge to regulate electronic structure, build accelerated electron transfer channels, and play a role in accelerating catalytic reactions.
[0037] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of the present invention carbonizes the surface of in-situ grown ZIF particles without destroying their morphology by heat treatment, thereby effectively improving the conductivity of the catalyst.
[0038] According to the present invention, the carbon nanotube film is also called carbon nanotube fiber. The carbon nanotube film can specifically be a single-walled carbon nanotube film or a multi-walled carbon nanotube film. As a preferred embodiment, the carbon nanotube film is a multi-walled carbon nanotube film. The use of a multi-walled carbon nanotube film allows the ZIF particles to be directly and densely distributed on the surface of the film. Compared with other types of carbon nanotubes, the contact resistance is smaller and more conducive to the passage of current; the diameter of the multi-walled carbon nanotube film can be selected in a wide range. As a preferred embodiment, the diameter of the multi-walled carbon nanotube film is 30-50nm, so that part of the carbon nanotubes can pass through the ZIF particles to play a fixing role and prevent them from falling off during the heat treatment process.
[0039] According to the present invention, ZIF8@ZIF67 / CNTF refers to ZIF8@ZIF67 particles doped with nickel and zinc attached to the surface of the carbon nanotube film, and ZIF8@ZIF67 particles refer to ZIF8 with Ni and Zn as the core coated by ZIF67 particles with Co as the core.
[0040] According to the present invention, the cobalt salt is a divalent salt of cobalt; the nickel salt is a divalent salt of nickel; the zinc salt is a divalent salt of zinc; the specific type of the salt is not limited, and it can be an inorganic salt, such as nitrate, sulfate, hydrochloride, or an organic salt such as acetate, etc. As a preferred embodiment, the cobalt salt, nickel salt, and zinc salt are all nitrates. Specifically, the cobalt salt is Co(NO3)2·6H2O, the nickel salt is Ni(NO3)2·6H2O, and the zinc salt is Zn(NO3)2·6H2O.
[0041] According to the present invention, the function of the dispersant is to promote the dispersion of the carbon nanotube film in the solvent, so that the dispersion is more uniform. There are many optional types of dispersants, as long as they can promote the dispersion of the carbon nanotube film in the solvent. The dispersant can be polyvinyl pyrrolidone, ethylenediaminetetramethylenephosphoric acid, polyacrylamide, etc. As a preferred embodiment, the dispersant is polyvinyl pyrrolidone (PVP), which has a better dispersion effect on the carbon nanotube film in the solvent.
[0042] According to the present invention, the function of the first solvent is to evenly disperse the carbon nanotube film and the cobalt salt, nickel salt and zinc salt. There are many types of first solvents to choose from, as long as the above substances can be evenly dispersed. The first solvent can be methanol, ethanol, isopropanol, etc. As a preferred embodiment, the first solvent is methanol, which has a better dispersion effect on each component.
[0043] According to the present invention, the optional ratio range of cobalt salt, nickel salt and zinc salt is relatively wide. Preferably, the proportion of Co in cobalt salt, nickel salt and zinc salt is 2+ 、Ni 2+ 、Zn 2+ The molar ratio of Co is 2:(1-1.5):(1-1.5); further preferably, Co 2+ 、Ni 2+ 、Zn2+ The molar ratio of Co is 2:1:1. 2+ As the reaction center of electrochemical catalysis, Ni 2+ 、Zn 2+ It plays a role in regulating the electronic structure. Overdoping and underdoping will affect Co 2+ The active center role of , when using this molar ratio, the doping amount is optimal and the activity of the obtained electrocatalyst is the best.
[0044] According to the present invention, the carbon nanotube film and the cobalt salt Co 2+ The molar ratio of carbon nanotube film to cobalt salt is preferably 2+ The molar ratio of the carbon nanotube film and the cobalt salt is (1-3): 1; further preferably, the carbon nanotube film and the cobalt salt Co 2+ The molar ratio of is 2:1. When this molar ratio is used, the electrocatalyst obtained has the densest distribution.
[0045] According to the present invention, dimethylimidazole and Co in cobalt salt 2+ The molar ratio of dimethylimidazole to cobalt salt is preferably selected in a wide range. 2+ The molar ratio of dimethylimidazole to cobalt salt is (1-2.5):1; further preferably, 2+ The molar ratio is 2: 1. When this molar ratio is used, the diameter of the prepared electrocatalyst is about 500nm, it is not easy to fall off, and the catalytic performance is the best.
[0046] According to the present invention, in the first solution, Co 2+ The concentration range of Co is relatively wide. 2+ The concentration of Co is 0.05-0.2 mol / L; further preferably, 2+ The concentration is 0.1 mol / L.
[0047] According to the present invention, the dosage of the dispersant can be selected in a wide range. Preferably, the mass ratio of the dispersant to the carbon nanotube film is 10:1.
[0048] According to the present invention, the function of the second solvent is to disperse the dimethylimidazole evenly. There are many types of second solvents to choose from, as long as the dimethylimidazole can be dispersed evenly. The second solvent can be methanol, ethanol, isopropanol, etc. As a preferred embodiment, the second solvent is methanol, which has a better dispersion effect on dimethylimidazole.
[0049] According to the present invention, in the second solution, the concentration of the carbon nanotube film can be selected in a wide range. Preferably, the concentration of the carbon nanotube film is 0.01-0.2 mol / L; more preferably, the concentration of the carbon nanotube film is 0.1 mol / L.
[0050] According to the present invention, preferably, the carbon nanotube film is pickled before step S1. The effect of pickling is to oxidize the hydroxyl groups on the surface of the carbon nanotube film to carboxyl groups, which is more conducive to the attachment of ZIF particles on its surface. There are many optional types of acids used for pickling. Preferably, the pickling is completed with a mixed acid solution, and the mixed acid solution is a mixture of HNO3 solution and H2SO4 solution. The volume ratio of HNO3 solution to H2SO4 solution can be selected in a wide range. Preferably, the volume ratio of HNO3 solution to H2SO4 solution is 3:1. The HNO3 solution preferably has a mass fraction of 65% to 68% HNO3, and the H2SO4 solution preferably has a mass fraction of 95% to 98% H2SO4.
[0051] Furthermore, the specific operation of the pickling process is not limited, as long as the acid is brought into contact with the carbon nanotube film. Preferably, the carbon nanotube film is added to the acid solution and stirred. Furthermore, the carbon nanotube film after pickling is cleaned and dried. The stirring, cleaning and drying operations belong to conventional operations in the art and are not limited.
[0052] According to the present invention, in step S1, the order in which the substances are dispersed in the first solvent is not limited, and they can be added simultaneously or in batches. Preferably, the carbon nanotube film and the dispersant are first added to the first solvent, and after being evenly dispersed, cobalt salt, nickel salt, and zinc salt are added for dispersion. The dispersion method is not limited, for example, one or a combination of magnetic stirring, stirring bar stirring, ultrasonic dispersion, etc. can be used. Preferably, the carbon nanotube film and the dispersant are first added to the first solvent for ultrasonication, and after being evenly dispersed, cobalt salt, nickel salt, and zinc salt are added for magnetic stirring to obtain a first solution.
[0053] According to the present invention, in step S2, the dispersing method of dimethylimidazole in the second solvent is not limited, for example, magnetic stirring, stirring bar stirring, ultrasonic dispersion, etc., or a combination of several methods can be used.
[0054] According to the present invention, in step S3, the first solution is added to the second solution preferably by a quick pouring method.
[0055] According to the present invention, preferably, the temperature of the hydrothermal reaction in step S4 is 70-110° C. and the time is 5-7 hours. Further preferably, the temperature of the hydrothermal reaction is 90° C. and the time is 6 hours.
[0056] According to the present invention, the separation method of the solid product in step S4 can be centrifugal separation, filtration, etc., preferably centrifugal separation is used for separation.
[0057] According to the present invention, preferably, the separated solid product is also washed and dried. Preferably, ethanol and deionized water are used for washing, respectively. Preferably, vacuum drying is used for drying.
[0058] According to the present invention, the inert atmosphere during calcination in step S5 is preferably nitrogen. Nitrogen is introduced during the heat treatment process. The synergistic effect of the carbon core on the surface of the product and the nitrogen element can further improve the conductivity of the material and accelerate the catalytic reaction.
[0059] According to the present invention, preferably, the calcination condition is to heat the catalyst to 600-950°C at a heating rate of 1-2.5°C / min and calcine for 2-6h. Further preferably, the calcination condition is to heat the catalyst to 700°C at a heating rate of 2°C / min and calcine for 2h. Too high an annealing temperature will destroy the surface structure of the catalyst and seriously affect the stability; too low an annealing temperature will not allow the surface to be sufficiently carbonized, affecting the conduction of the current. By adopting this calcination system, the morphology of the obtained electrocatalyst can be maintained well and the catalytic performance can be the highest. Heating at a heating rate of 2°C / min can prevent uneven heating due to excessively rapid heating, which affects the degree of carbonization.
[0060] The second aspect of the present invention provides a zeolite imidazolate framework-derived electrocatalyst prepared by the above-mentioned preparation method.
[0061] The third aspect of the present invention provides an application of the above-mentioned zeolite imidazolate framework-derived electrocatalyst for catalytic electrolysis of water to produce hydrogen and / or oxygen.
[0062] Example
[0063] All reagents used in the following examples and comparative examples are commercially available.
[0064] Example 1
[0065] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of this embodiment comprises the following steps:
[0066] Step 1: Prepare a mixed acid solution: mix 30 mL of 65% to 68% HNO3 and 10 mL of 95% to 98% H2SO4 in a volume ratio of 3:1, and then stir magnetically for 1 hour;
[0067] Step 2, acid-washing carbon nanotube film: weigh 40 mg of multi-walled carbon nanotube film with a diameter of 30-50 nm, add it to the above mixed acid solution, stir for 10 minutes until it is uniform, and then magnetically stir at 80°C for 3 hours, then take it out, wash it with deionized water 3 times, and dry it in a drying oven at 65°C for 12 hours;
[0068] Step 3: 40 mg of the acid-washed multi-walled carbon nanotube film and 48 mg of PVP were dispersed in 10 mL of methanol solution and ultrasonicated for 1 h, followed by adding 116 mg of Co(NO3)2·6H2O, 59 mg of Ni(NO3)2·6H2O and 61 mg of Zn(NO3)2·6H2O, and magnetically stirred at room temperature for 1 h to obtain solution A;
[0069] Step 4: Disperse 76.4 mg of dimethylimidazole in 10 mL of methanol solution and stir magnetically at room temperature for 1 h to obtain solution B;
[0070] Step 5: Quickly pour solution A into solution B and stir magnetically at room temperature for 20 minutes to prepare the precursor solution;
[0071] Step 6: Preparation of ZIF8@ZIF67 / CNTF: Place the above precursor solution in a reactor, heat to 90°C and react for 6 hours, then cool to room temperature. Then, wash the solid product ZIF8@ZIF67 / CNTF with ethanol and deionized water by centrifugation, and dry it in vacuum at 75°C for 12 hours.
[0072] Step 7: Annealing: The ZIF8@ZIF67 / CNTF product obtained above was placed in a tube furnace, heated to 700°C at a flow rate of 100 sccm under N2 atmosphere for 2 h at a rate of 2°C / min, and then cooled to room temperature. The product was labeled Co-Ni-Zn / NCNTF.
[0073] Example 2
[0074] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 in other steps and raw material ratios, except that: in step 3, 93.5 mg Co(NO3)2·6H2O, 70.1 mg Ni(NO3)2·6H2O and 71.6 mg Zn(NO3)2·6H2O are added, i.e., Co 2+ 、Ni 2+ 、Zn 2+ The total molar amount remains unchanged, and the molar ratio of the three is adjusted to 2:1.5:1.5.
[0075] Example 3
[0076] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 3, 103.9 mg Co(NO3)2·6H2O, 51.9 mg Ni(NO3)2·6H2O and 79.5 mg Zn(NO3)2·6H2O are added, i.e., Co 2+ 、Ni 2+ 、Zn 2+ The total molar amount remains unchanged, and the molar ratio of the three is adjusted to 2:1:1.5.
[0077] Example 4
[0078] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 3, 103.9 mg Co(NO3)2·6H2O, 77.3 mg Ni(NO3)2·6H2O and 52.6 mg Zn(NO3)2·6H2O are added, i.e., Co 2+ 、Ni 2+ 、Zn 2+ The total molar amount remains unchanged, and the molar ratio of the three is adjusted to 2:1.5:1.
[0079] Example 5
[0080] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 3, 104.7 mg Co(NO3)2·6H2O, 104.7 mg Ni(NO3)2·6H2O and 106.9 mg Zn(NO3)2·6H2O are added, i.e., Co 2+ 、Ni 2+ 、Zn 2+ The total molar amount remains unchanged, and the molar ratio of the three is adjusted to 1:1:1.
[0081] Example 6
[0082] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 3, 140 mg Co(NO3)2·6H2O, 46.7 mg Ni(NO3)2·6H2O and 47.7 mg Zn(NO3)2·6H2O are added, i.e., Co 2+ 、Ni 2+ 、Zn 2+ The total molar amount remains unchanged, and the molar ratio of the three is adjusted to 3:1:1.
[0083] Example 7
[0084] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 4, 95.5 mg of dimethylimidazole is added, that is, dimethylimidazole and Co in cobalt salt are reacted. 2+ The molar ratio is 2.5:1.
[0085] Example 8
[0086] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 4, 38.2 mg of dimethylimidazole is added, that is, dimethylimidazole and Co in the cobalt salt are reacted.2+ The molar ratio is 1:1.
[0087] Example 9
[0088] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 4, 19.1 mg of dimethylimidazole is added, that is, dimethylimidazole and Co in the cobalt salt are reacted. 2+ The molar ratio is 1:2.
[0089] Example 10
[0090] The preparation method of the zeolite imidazolate skeleton-derived electrocatalyst of this embodiment is the same as that of Example 1 except that: in step 4, 114.6 mg of dimethylimidazole is added, that is, dimethylimidazole and Co in the cobalt salt are reacted. 2+ The molar ratio is 3:1.
[0091] Embodiment 11
[0092] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of this embodiment is the same as that of Example 1 in other steps, except that the calcination condition is to increase the temperature to 600° C. at a heating rate of 3.5° C. / min and calcine for 4 hours.
[0093] Example 12
[0094] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of this embodiment is the same as that of Example 1 in other steps, except that the calcination condition is to increase the temperature to 600° C. at a heating rate of 3.5° C. / min and calcine for 6 h.
[0095] Embodiment 13
[0096] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of this embodiment is the same as that of Example 1 in other steps, except that the calcination condition is to increase the temperature to 600° C. at a heating rate of 3.5° C. / min and calcine for 2 h.
[0097] Embodiment 14
[0098] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of this embodiment is the same as that of Example 1 in other steps, except that the calcination condition is to increase the temperature to 600° C. at a heating rate of 3.5° C. / min and calcine for 8 h.
[0099] Embodiment 15
[0100] The preparation method of the zeolite imidazolate framework-derived electrocatalyst of this embodiment is the same as that of Example 1 in other steps, except that the calcination condition is to heat the temperature to 950° C. at a heating rate of 3.5° C. / min and calcine for 2 h.
[0101] Comparative Example 1
[0102] This comparative example is a blank control of a multi-walled carbon nanotube film, and the preparation method comprises the following steps:
[0103] Step 1: Prepare a mixed acid solution: mix 30 mL of 65% to 68% HNO3 and 10 mL of 95% to 98% H2SO4 in a volume ratio of 3:1, and then stir magnetically for 1 hour;
[0104] Step 2, acid-washing carbon nanotube film: weigh 40 mg of multi-walled carbon nanotube film with a diameter of 30-50 nm, add it to the above mixed acid solution, stir for 10 minutes until it is uniform, and then magnetically stir at 80°C for 3 hours, then take it out, wash it with deionized water 3 times, and dry it in a drying oven at 65°C for 12 hours;
[0105] Step 3, annealing: the acid-washed multi-walled carbon nanotube film obtained above is placed in a tubular furnace, heated to 700°C at a flow rate of 100 sccm under a N2 atmosphere for 2 h at a rate of 2°C / min, and then cooled to room temperature. The product is labeled CNTF.
[0106] Comparative Example 2
[0107] This comparative example is Ni 2+ The single-doped zeolite imidazolate framework-derived electrocatalyst is prepared by a method comprising the following steps:
[0108] Step 1: Prepare a mixed acid solution: mix 30 mL of 65% to 68% HNO3 and 10 mL of 95% to 98% H2SO4 in a volume ratio of 3:1, and then stir magnetically for 1 hour;
[0109] Step 2, acid-washing carbon nanotube film: weigh 40 mg of multi-walled carbon nanotube film with a diameter of 30-50 nm, add it to the above mixed acid solution, stir for 10 minutes until it is uniform, and then magnetically stir at 80°C for 3 hours, then take it out, wash it with deionized water 3 times, and dry it in a drying oven at 65°C for 12 hours;
[0110] Step 3: Disperse 40 mg of the acid-washed multi-walled carbon nanotube film and 48 mg of PVP in 10 mL of methanol solution and ultrasonicate for 1 h, then add 116 mg of Co(NO3)2·6H2O and 59 mg of Ni(NO3)2·6H2O, and stir magnetically at room temperature for 1 h to obtain solution A;
[0111] Step 4: Disperse 325 mg of dimethylimidazole in 10 mL of methanol solution and stir magnetically at room temperature for 1 h to obtain solution B;
[0112] Step 5: Quickly pour solution A into solution B and stir magnetically at room temperature for 20 minutes to prepare the precursor solution;
[0113] Step 6: Preparation of ZIF8@ZIF67 / CNTF: Place the above precursor solution in a reactor, heat to 90°C and react for 6 hours, then cool to room temperature. Then, wash the solid product ZIF8@ZIF67 / CNTF with ethanol and deionized water by centrifugation, and dry it in a vacuum at 75°C for 12 hours.
[0114] Step 7: Annealing: The ZIF8@ZIF67 / CNTF product obtained above was placed in a tube furnace, heated to 700°C at a flow rate of 100 sccm under a N2 atmosphere for 2 h at a rate of 2°C / min, and then cooled to room temperature. The product was labeled Co-Ni / NCNTF.
[0115] Comparative Example 3
[0116] This comparative example is Zn 2+ The single-doped zeolite imidazolate framework-derived electrocatalyst is prepared by a method comprising the following steps:
[0117] Step 1: Prepare a mixed acid solution: mix 30 mL of 65% to 68% HNO3 and 10 mL of 95% to 98% H2SO4 in a volume ratio of 3:1, and then stir magnetically for 1 hour;
[0118] Step 2, acid-washing carbon nanotube film: weigh 40 mg of multi-walled carbon nanotube film with a diameter of 30-50 nm, add it to the above mixed acid solution, stir for 10 minutes until it is uniform, and then magnetically stir at 80°C for 3 hours, then take it out, wash it with deionized water 3 times, and dry it in a drying oven at 65°C for 12 hours;
[0119] Step 3: Disperse 40 mg of the acid-washed multi-walled carbon nanotube film and 48 mg of PVP in 10 mL of methanol solution and ultrasonicate for 1 h, then add 116 mg of Co(NO3)2·6H2O and 58 mg of Zn(NO3)2·6H2O, and stir magnetically at room temperature for 1 h to obtain solution A;
[0120] Step 4: Disperse 325 mg of dimethylimidazole in 10 mL of methanol solution and stir magnetically at room temperature for 1 h to obtain solution B;
[0121] Step 5: Quickly pour solution A into solution B and stir magnetically at room temperature for 20 minutes to prepare the precursor solution;
[0122] Step 6: Preparation of ZIF8@ZIF67 / CNTF: Place the above precursor solution in a reactor, heat to 90°C and react for 6 hours, then cool to room temperature. Then, wash the solid product ZIF8@ZIF67 / CNT with ethanol and deionized water by centrifugation, and dry in vacuum at 75°C for 12 hours.
[0123] Step 7: Annealing: The ZIF8@ZIF67 / CNTF product obtained above was placed in a tube furnace, heated to 700°C at a flow rate of 100 sccm under N2 atmosphere for 2 h at a rate of 2°C / min, and then cooled to room temperature. The product was labeled Co-Zn / NCNTF.
[0124] Structural characterization and performance testing
[0125] The ZIF-derived electrocatalysts obtained in the above-mentioned embodiments and comparative examples were tested by scanning electron microscopy. Figure 1 , Figure 2 , Figure 3 Ni 2+ Single doping (Comparative Example 2), Zn 2+ Single doping (Comparative Example 3) and Ni 2+ 、Zn 2+ From the morphology scanning electron microscopy image of the electrocatalyst of dual ion doping (Example 1), it can be seen that each zeolite imidazolate framework-derived electrocatalyst presents a complete structure in the shape of a regular rhombic dodecahedron.
[0126] The HER performance of the ZIF-derived electrocatalysts obtained in the above embodiments and comparative examples was tested. Figure 4 HER polarization curves of the single-doped and double-doped zeolite imidazolate framework-derived electrocatalysts. It can be seen that the hydrogen evolution performance of the double-doped catalyst is significantly improved. The OER performance of the ZIF-derived electrocatalysts obtained in the above embodiments and comparative examples is tested. Figure 5 Figure 2 shows the OER polarization curves of the electrocatalyst derived from the single-doped and double-doped zeolite imidazolate framework. It can be seen that the oxygen evolution performance of the double-doped catalyst is significantly improved. When the hydrogen evolution current density reaches 10 mA / cm 2 When the overpotential is 114mv; when the hydrogen evolution current density reaches 50mA / cm 2 When the overpotential is 276mv, the Tafel slope is 92.6mv / dec. When the oxygen evolution current density reaches 10mA / cm 2 When the overpotential is 289mv, when the oxygen evolution current density reaches 50mA / cm 2 The overpotential is 378mv; the Tafel slope is 101.6mv / dec. The following table 1 shows the hydrogen evolution current density of the electrocatalysts obtained in each embodiment and comparative example reaching 10mA / cm 2 , 50mA / cm 2 The overpotential of oxygen evolution reaches 10mA / cm 2 , 50mA / cm 2At the same current density, the lower the overpotential, the less energy is required to reach the corresponding current density, and the better the catalytic performance of the catalyst. It can be seen from the data in the following table that the Ni 2+ 、Zn 2+ The catalytic performance of the ion dual-doped catalyst is better than that of the single-doped catalysts in Comparative Examples 2 and 3. 2+ 、Ni 2+ 、Zn 2+ The catalytic performance of the catalysts in Examples 1-4 is significantly better than that in Examples 5 and 6, which are preferred embodiments; Examples 1 and 7-10 are different in that the molar ratio of dimethylimidazole in the raw material and Co in the cobalt salt is 2+ The molar ratios are different, among which the catalytic performance of the catalysts of Examples 1, 7 and 8 is significantly better than that of Examples 9 and 10, which are preferred implementations; Examples 11-13, 14 and 15 are distinguished by different calcination times and temperatures, and the catalytic performance of the catalysts of Examples 11-13 and 15 is better than that of Example 14, which is a preferred implementation.
[0127] Table 1
[0128]
[0129] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.
Claims
1. A method for preparing a zeolite imidazolate framework-derived electrocatalyst, characterized in that: The following steps are involved: S1. dispersing the carbon nanotube film, the dispersant, the cobalt salt, the nickel salt, and the zinc salt in a first solvent to obtain a first solution; S2. dispersing dimethylimidazole in a second solvent to obtain a second solution; S3. adding the first solution to the second solution to obtain a precursor solution; S4. subjecting the precursor solution to a hydrothermal reaction to obtain a hydrothermal reaction product of ZIF8@ZIF67 / CNTF; S5. calcining ZIF8@ZIF67 / CNTF under an inert atmosphere to obtain the zeolite imidazolate framework-derived electrocatalyst.
2. The preparation method according to claim 1, characterized in that: The carbon nanotube film is a multi-walled carbon nanotube film.
3. The preparation method according to claim 1, characterized in that: The Co in the cobalt salt 2+ , Ni in the nickel salt 2+ and Zn in the zinc salt 2+ The molar ratio between them is 2:(1-1.5):(1-1.5); The carbon nanotube film and the cobalt salt 2+ The molar ratio is (1~3):
1.
4. The preparation method according to claim 1, characterized in that: The first solvent and / or the second solvent is methanol; The dispersant is polyvinyl pyrrolidone.
5. The preparation method according to claim 1, characterized in that: Dimethylimidazole and Co in the cobalt salt 2+ The molar ratio is (1~2.5):
1.
6. The preparation method according to claim 1, characterized in that: The method further includes, before step S1, acid washing the carbon nanotube film.
7. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 70-110° C. and the time is 5-7 hours.
8. The preparation method according to claim 1, characterized in that: In step S5, the inert atmosphere is nitrogen; the calcination conditions are heating to 600-950° C. at a heating rate of 1.5-5° C. / min and calcining for 2-6 hours.
9. A zeolite imidazolate framework derived electrocatalyst, characterized in that: The method is prepared by any one of claims 1 to 8.
10. A use of the zeolite imidazolate framework derived electrocatalyst as claimed in claim 9, characterized in that: Used for catalytic electrolysis of water to produce hydrogen and / or oxygen.
Citation Information
Patent Citations
Method for synthesis of double-casing layer carbon nanometer hollow polyhedron by metal-organic framework as template
CN105110315A
Preparation method of one-dimensional porous carbon nanotube
CN106829924A